Critical Analysis of Technologies Enhancing Supply Chain Collaboration in the Food Industry: A Nigerian Survey - Ebenezer Akinbamini; Alix Vargas; Angela Traill; Andrés Boza; Llanos Cuenca (Logistics, 2025)
Background: Supply chain collaboration technologies (SCCTs) are digital tools designed to enhance communication, coordination, and integration among supply chain stakeholders. These tools are essential for enhancing transparency, efficiency, and traceability within complex supply chain networks, particularly in the food industry. Methods: This study focuses on the statistical analysis of survey data to evaluate the adoption and impact of SCCTs, including blockchain, Internet of Things (IoT), enterprise resource planning (ERP), and artificial intelligence (AI), in Nigeria’s food industry. Results: The results reveal critical insights into the adoption barriers, perceived benefits, and gaps in implementation. Descriptive and inferential statistical techniques highlight significant variations in technology across different sectors, uncovering key factors influencing the integration of SCCTs. The findings demonstrate that while the technologies hold substantial potential to optimize supply chain performance, their acceptance is constrained by infrastructural deficiencies, regulatory challenges, under-developed trust-building mechanisms, and limited technical expertise. Conclusions: This paper underscores the importance of targeted interventions, policy support, and resource allocation to foster the effective utilization of SCCTs. The study provides data-driven recommendations for improving technology uptake, contributing to the sustainability and competitiveness of Nigeria’s food supply chain.